2009
DOI: 10.1186/1471-2407-9-101
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of recurrent malignant gliomas with fotemustine monotherapy: impact of dose and correlation with MGMT promoter methylation

Abstract: BackgroundIn recurrent malignant gliomas (MGs), a high rate of haematological toxicity is observed with the use of fotemustine at the conventional schedule (100 mg/m2 weekly for 3 consecutive weeks followed by triweekly administration after a 5-week rest period). Also, the impact of O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation status on fotemustine activity has never been explored in the clinical setting.Methods40 patients with recurrent pretreated MG were identified as being treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 25 publications
0
29
1
Order By: Relevance
“…Fotemustine, a third generation chloroethylnitrosourea given to recurrent glioma patients after TMZ failure showed very promising results and limited toxicity in three recent studies from Italy [49][50][51]. In addition, like other alkylating agents, fotemustine appears more effective in patients with O6-methylguanine-DNA methyltransferase (MGMT) gene promoter methylation [49].…”
Section: Fotemustinementioning
confidence: 99%
“…Fotemustine, a third generation chloroethylnitrosourea given to recurrent glioma patients after TMZ failure showed very promising results and limited toxicity in three recent studies from Italy [49][50][51]. In addition, like other alkylating agents, fotemustine appears more effective in patients with O6-methylguanine-DNA methyltransferase (MGMT) gene promoter methylation [49].…”
Section: Fotemustinementioning
confidence: 99%
“…These data are interesting if we consider that the majority of the patients had a poor performance status with a compromised hematological status ( Table 1). The results showed that the toxicity incidence rate of fotemustine has a peak in correspondence of the induction completion and, it increases with the number of completed cycles [6]. In the trial by Brandes et al patients with progressive GBM after radiotherapy plus concomitant and/or adjuvant temozolomide received 3-weekly doses (100-75 mg m 2 ) of fotemustine followed, after a 5-week rest, by fotemustine (100 mg m 2 ) every 3 weeks.…”
mentioning
confidence: 99%
“…The clinical trial by Fabi et al did not suggest any correlation between MMGT methylation status and response [6]. However, this study enrolled also anaplastic tumors and the analysis of MMGT promoter was performed in less that 50% of cases.…”
mentioning
confidence: 99%
See 2 more Smart Citations